Acute stress improves analogical reasoning: examining the roles of stress hormones and long-term memory. (10th September 2020) - Smith, Amy M.; Elliott, Grace; Hughes, Gregory I.; Feinn, Richard S.; Brunyé, Tad T.
Abstract: Analogical reasoning relies on subprocesses of long-term memory and problem-solving. Stress, with its accompanying hormones dehydroepiandrosterone (DHEA) and cortisol, has been shown to impair memory retrieval but potentially enhance problem solving. The present study combined Gick and Holyoak's Duncker's Radiation Problem with stress induction to determine the influence of stress on these two components of analogical reasoning. Participants ( N = 131) learned an analog story and returned a day later for a stressful or non-stressful task. They then completed three consecutive tests: a spontaneous attempt at Duncker's Problem, a recall test for the analog, and another attempt at Duncker's Problem using analogical reasoning. Stress did not influence spontaneous problem-solving or story recall but did improve performance on the second attempt at Duncker's Problem. Further, performance trended toward a positive association with DHEA. Thus, stress and increases in DHEA may enhance identification and use of an analog to solve a problem.